Do social phobia and depression go hand in hand? A cross-sectional study among school-going adolescents of Northern region of India - Kezia Gupta; Jayanti Semwal; Neha Sharma; Abhay Srivastava; Shaili Vyas (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The preeminent mental health conditions, namely social phobia and depression among adolescents, usually remain incognito. The transition period from childhood to adulthood makes adolescents more liable for low amour-propre, loneliness, and even increases the suicidal tendencies among them. To burgeon the knowledge regarding social phobia and depression among adolescents, the present study was put forward with the objective to assess the prevalence of social anxiety disorders (social phobia) and depression among adolescents. MATERIALS AND METHODS: A cross-sectional study was conducted for 2 months on 600 students aged 10-19 years belonging to classes VIII-XII of government and private schools in the Dehradun district recruited through multistage random sampling technique. A pre-tested semi-structured questionnaire having sociodemographic details, validated self-administered tools, Social Phobia Inventory tool, and Kutchers Adolescent Depression Scale (Cronbach's alpha: 0.77 and 0.79) were used. Statistical package for social sciences, version 23 was used for data analysis. Chi-square test, Fisher exact test, and Pearson correlation analysis were used for analysis RESULTS: Prevalence of social phobia was found to be 37% among school-going adolescents. Further, 23.7% of the study participants had mild social phobia, while moderate and severe phobia was seen among 11.5% and 2.3%, respectively. Females had more moderate and severe social phobia than males. Adolescents of government schools had more moderate affective distress and somatic distress as compared to adolescents of private schools. CONCLUSION: Social phobia and depression among school-going adolescents are on the upsurge. The present study shows that social phobia and depression have a strong correlation among themselves, which needs to be addressed as expeditiously as possible. Coping strategies and social skill therapy and programs are pressing priorities for the fulgent future of adolescents.